The removal of pluto from the class of planets and homosexuality from the class of psychiatric disorders: a comparison - Zachar Peter (Philosophy, Ethics, and Humanities in Medicine, 2012)
Abstract We compare astronomers' removal of Pluto from the listing of planets and psychiatrists' removal of homosexuality from the listing of mental disorders. Although the political maneuverings that emerged in both controversies are less than scientifically ideal, we argue that competition for "scientific authority" among competing groups is a normal part of scientific progress. In both cases, a complicated relationship between abstract constructs and evidence made the classification problem thorny.